The Relationship Between Self efficacy With The Ability Of Daily Living Activity Of Post-Stroke Patients - Ni Komang Suwandewi; Ni Luh Putu Thrisna Dewi; I Gusti Ngurah Ketut Sukadarma; Ni Made Nopita Wati (Caring : Jurnal Keperawatan, 2021)
Patient feel weak after stroke in the motor that causes patients to experience physical limitations, disability, stress, depression, decreased ability to perform self-care and decreasing ability to basic daily needs. Strong self-confidence can increase motivation and ability to do daily activities.This research attempts to figure out the relationship between self efficacy and the ability of daily living activity of patients after stroke in the Neurology Polyclinic at Sanglah Central General Hospital Denpasar.This research is a correlation analytic study with cross sectional approach. The sampling method used purposive sampling technique with the number of respondents 75 outpatients in the Neurology Polyclinic at Sanglah Central General Hospital Denpasar in November - December 2019. Data were collected by The Stroke Self efficacy Questionnaire, Barthel Index and analyzed by Spearmans Rank statistic test.The result of this research is obtained from 75 respondents, most of the self efficacy in post-stroke patients was moderate (57.3%) and the level of independence of daily living activity required minimal assistance (42.6%). Statistical tested indicate that there was a significant relationship between self efficacy and the ability of daily living activity of patients after stroke in the Neurology Polyclinic at Sanglah Central General Hospital Denpasar with the strength of a strong relationship between variables and the direction of a positive relationship (p value 0.002 <? 0.05, r = 0.713).